Social media and Undergraduates’ Study Time: The Counselling Implication - Pitan, Oluyemisi O. (West African Journal of Open and Flexible Learning, 2016)
The purpose of this study was to investigate the influence of social media on undergraduates’ study time. The study was guided by three research hypotheses. It involved a total sample of 229 undergraduate students from six faculties/schools in private universities who were randomly selected. Data was collected by using a questionnaire which had three scales; demographic section, undergraduates’ study time scale, and utilization of social media. All the items except the demographic variable are measured on a 5 continuum scale ranging from 1 to 5 (Strongly Disagree (1) to Strong Agree (5). Data collected were analysed using mean, standard deviation, t-test and ANOVA to answer the research questions and hypotheses. No significant gender differences were found among social media usage and undergraduates’ study time. It was recommended that counselling psychologists or guidance counsellors should create an awareness on applications of social media that are academic oriented so that both the students and the teachers can utilize them whenever they are online such as Evemote, google drive, Dropbox, and eBooks among others.